Use of augmented reality with game elements in education : literature review - Ređep, Tamara (Array, 2021)
This paper reviews the literature and analyzes the research topics on the use of augmented reality technology in education with possible integration of game elements, in order to obtain a synthesis of previous knowledge related to the topic in the period from 2010 to 2020. Fifty-two papers describing different aspects of augmented reality used in the field of education were selected for the analysis. The main conclusions of the systematization and synthesis were: a) five basic thematic categories were identified; b) 2019 was recognized as the year with the largest publication of papers; c) the use of augmented reality in teaching activities, and especially with game elements, improves student efficiency, stimulates attention and interest, brings improvements in collaboration and perception of fun, improves teaching and learning processes and in general encourages innovation and improvement through educational technology.